PENGARUH CASH POSITION, DEBT TO EQUITY RATIO DAN RETURN ON ASSETS TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR, Tbk PERIODE 2012 ÔÇô 2016 - jurnalpps pps; Weni Risqiana; Novrida Qudsi Lutfillah; Muninghar ÔÇì (Jurnal Manajerial Bisnis, 2018)
The objective of this research is to find out and analyzes the influences of Cash Position, Debt to Equity Ratio, and Return on Assets to Dividend Payout Ratio at manufactured industry period 2012 -2016. The data used in this research is from the yearly financial report in Indonesian Stock Exchange (IDX). The sample use is 7 industry of 149 listed manufactured industy at 2012 ÔÇô 2016. The analysis of method used in this research is the multiple linear regressions method, the hypothesize test used the stastistical of F-test and the stastistical of t-test. The results data analysis showed that all the independent variable, which Cash Position, Debt to Equity Ratio, and Return on Assets simultaneously have an influence on the Dividend Payout Ratio (DPR). At the determinant coefficient (R2) it shows that research independent variables able to explain 19,3% to Dividend Payout Ratio while the remaining of 80,7% explained by independent variables that were un-research. While partially (t-test), only the Return on Assets (ROA) which have an influence on the Dividend Payout Ratio (DPR). Keywords: cash position, debt to equity ratio (DER), return on assets (ROA), dividend payout ratio (DPR)